"Before the war we had it all": Family planning among couples in a post-conflict setting. Issue 8 (3rd August 2017) - Warren, Nicole; Alvarez, Carmen; Makambo, Maphie Tosha; Johnson-Agbakwu, Crista; Glass, Nancy
ABSTRACT: There is little evidence about family planning knowledge, attitudes, and use among couples in post-conflict Democratic Republic of the Congo. We used qualitative descriptions to analyze data from 75 participants. Intimate partner violence (IPV) was common among participants. They were aware of family planning methods; however, IPV and fears of side effects were barriers to use. Although participants were concerned about the cost of large families, had positive attitudes toward family planning, and intended to use it, actual use was uncommon. The need for family planning was acute because of war-related poverty. Couples negotiated, but men had strong influence over family planning decisions. Couples saw health workers as a valuable resource. Interventions in this setting should include a couple-based approach that addresses IPV as well as family planning content.